Why rapid urbanization process cannot improve employment absorption capacity of service industry in China – also on the interactive mode innovation between service industry development with urbanization under the background of transformation and upgrading - Shi-hong Zeng; Jie-chang Xia (China Finance and Economic Review, 2016)
Background: China is experiencing rapid urbanization and service industrial developement. Methods: In this paper, the relationship between urbanization and service employment is studied by using mathematical model and econometric test method. Results: This paper documents that there is a significant positive correlation between rapid urbanization process and services absorbing employment ability by the regression result using time-series data since China's reform and opening up. China's urbanization process cannot become the Granger causes that service employment absorption capacity to improve by analyzing the SVAR model and Granger causality test. Conclusions: So, Chinese urbanization patterns should transform from rapid industry park construction to increased service employment density of city.
Keywords: 330; Service employment absorption capacity; Transformation of urban functions; Service employment density of the city